Short term groupwork in the treatment of chronic sorrow: A Norwegian experience - Engebrigtsen, Gerd Kramm; Heap, Ken (Groupwork)
This article describes the use of short term groupwork in supporting parents of children with a congenital progressive terminal disease. Both content and group process are exemplified and they provide a basis for exploring the needs of persons suffering chronic sorrow. It is suggested that short term groupwork may both support and extend members’ ways of coping. Publisher’s note: We are now putting all back issues of Groupwork on line. Articles in this issue have been scanned to pdf files as viable original typesetting files no longer exist. Though they may not look it, these files are to some extents earchable. This issue was published nearly 30 years ago. We have stated author professional details as received at time of publication.